Bundling of feed and forage innovations in Central Ethiopia and Amhara regions - Mekonnen, Kindu; Gebreyes, Million; Alene, Temesgen; Tessema, Fikadu; Alemayehu, Liulseged; Amare, Fikadu; Getachew, Tesfa; Seifu, Haimanot (International Livestock Research Institute, 2025)
Livestock feed resources in Ethiopia are primarily derived from natural pasture, crop residues, crop aftermath, fodder trees, and shrubs, with additional contributions from agro-industrial by-products, improved forage crops, and cultivated pastures. However, during the dry season, both crop residues and natural pastures are typically low in crude protein, vitamins, and metabolizable energy, resulting in reduced livestock productivity and poor reproductive performance. Therefore, integrating feed and forage innovations into existing crop-livestock production systems is crucial.